The comparative value of shelled corn and sorghum grain prepared by different milling processes for finishing fall pigs drylot - Aubel, C.E. (Kansas Agricultural Experiment Station, 2011)
Grain sorghums are being grown extensively in many parts of the High Plains. Sorghum grain previously has given excellent results compared with corn in feeding tests with swine at this station. New ways of processing grain may improve the efficiency of the grains for feeding and thus provide more profit in hog raising. Five lots of pigs were self-fed, free choice, in drylot. All lots received a mixed animal and plant protein supplement of 4 parts tankage, 4 parts soybean meal, 1 part cottonseed meal, and 1 part alfalfa meal. Each ton of mixed protein supplement also contained 27 pounds of Aurofac and one half pound of zinc oxide. The ration for each lot varied only in the method of processing.
Keywords: Swine; Shelled corn; Sorghum grain; Milling